2012
DOI: 10.4038/vingnanam.v10i1.4072
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Kinetic Properties of Crude and Purified Xylanase from <i>Bacillus pumilus</i> with Commercial Xylanase from <i>Aspergillus niger</i>

Abstract: Xylanases showing better stability at alkaline pH and higher temperatures have potential applications in several industrial processes. The objective of this study is to compare the kinetic properties and stability of crude and purified xylanase from Bacillus pumilus with commercial xylanase from Aspergillus niger. Bacillus pumilus which can grow and produce xylanase above 40 o C and pH 9.0 was selected for this study. Crude, purified and commercial xylanases showed zero order kinetics for 10 minutes and highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Different ionizable groups with different p K a values are present on the surface of the protein molecules and surface charge distribution on the enzyme molecules varies with the pH on the environment. These fluctuations in charges may affect the enzyme activity either by changing the structure or by changing the charge of a residue important for substrate binding or catalysis [ 50 ]. The removal of proteases and protein fragments frequently present in the crude extract, which in some cases can be considered enzyme-stabilizing substances, can make the enzyme more susceptible to pH changes [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different ionizable groups with different p K a values are present on the surface of the protein molecules and surface charge distribution on the enzyme molecules varies with the pH on the environment. These fluctuations in charges may affect the enzyme activity either by changing the structure or by changing the charge of a residue important for substrate binding or catalysis [ 50 ]. The removal of proteases and protein fragments frequently present in the crude extract, which in some cases can be considered enzyme-stabilizing substances, can make the enzyme more susceptible to pH changes [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study a Bacillus pumilus strain showed maximum xylanase production after 20 h using birchwood xylan (Duarte et al, 1999). Kapilan and Arasaratnam (2012) isolated B. subtilis from soil which exhibit highest xylanase activity after 42 h in SmF.…”
Section: Time Course Study For Xylanase Productionmentioning
confidence: 99%